Transverse Colorectal Carcinoma Imaging: A Case Report - Langko, Jovita Marlin; Atmaja , Muhammad Hidayat Surya; Laraswati, Budi (Open Access Macedonian Journal of Medical Sciences, 2022)
Colorectal cancer (CRC) is a type of malignancy in the digestive system. Colorectal cancer can be found anywhere along the large intestine from the cecum to the rectum. However, transverse colorectal cancer is a rare case and is only found in 6.8% of total colorectal cancers. A 64-year-old male patient with complaints of weakness, changes in the pattern of defecation, namely dark brown bowel movements for approximately +/- 8 months, anemia, and an increase in serum CEA. The results of the initial examination with plain abdominal radiographs did not reveal any abnormalities, only normal gas shadows mixed with fecal material were found that were prominent in the right to left hypochondrium region. After further examination, the patient was found to have stage 4 transverse colorectal cancer. The diagnosis of transverse colorectal carcinoma (CRC) was established based on fluoroscopy findings which showed filling abnormalities and colonic lumen irregularities in the medial 1/3 of the transverse colon forming an apple core image with the narrowest diameter + /- 3 mm along +/- 6 cm, shouldering sign (+), and on CT abdomen with contrast, an intraluminal malignant mass was found (Staging AJCC 8th ed 2018 T4aN2aM0). The diagnosis of CRC was confirmed by the results of resection and histopathological examination which found well-differentiated adenocarcinoma of the colon.